Avaliação do efeito da Doxiciclina associada ou não à decametasone no modelo de reparo ósseo alveolar em ratos - Gomes, Kátia do Nascimento (2015)
The alveolar bone repair model, through dental excision in rats, allows the longitudinal study of local and systemic parameters. This allows learning the pathophysiology in inflammatory bone remodeling process. The objective of the research was to investigate the effect of doxycycline associated or not with dexamethasone on the events that follow the bone reabsorption process in alveolar bone repair in rats. The animals (190-200 g) were treated daily (per os) with saline solution Control (SSC), doxycycline (DOX 10 and 25 mg/kg), Dexamethasone (DEXA 1 mg/kg) (IP), and sacrificed according to experimental group (7, 14 and 21 days) to remove their jaws, which were used in the qualitative analysis of microstructural parameters, histomorphometry, and immunohistochemistry for Wnt10b and Dkk-1. It was observed that DOX (10 and 25 mg / kg ) improve some parameters such as the number of osteoblasts increase, reduction in the number of osteoblasts and % increase in bone tissue compared to the CTL group. The results also showed an increase in the expression of Wnt 10b, and Dkk-1 reduction, during the process of bone repair in animals that received DOX (10 and 25 mg/kg), compared to groups CTL. These findings suggest that DOX offers osteoinductive and osteoprotector effects on bone tissue during the alveolar bone remodeling process. It is possible that, in addition to anti-inflammatory effects recognized in DOX, this Tetracycline can influence the expression of Wnt 10b, favoring bone neoformation, and modulate the expression of Dkk-1, inhibiting tissue resorption in the alveolus of the animals.